The effects of education-job (mis)match on the earnings of graduates in the Czech Republic - Jan Sedláček; Martin Zelenka (Review of Economic Perspectives, 2021)
This paper deals with the effects of education-job (mis)match on the earnings of higher education graduates in the context of higher education expansion and different phases of the economic cycle in the Czech Republic in 2006-2018. It aims to contribute to knowledge about the effects of education-job (mis)match on earnings in two ways. First, it concentrates on both the vertical and the horizontal dimensions of education-job (mis)match. Second, it considers the effects of contextual variables: the share of graduates in the population and the unemployment rate of graduates. The paper is based on assumptions derived from assignment theory. The authors use data of graduates' self-evaluation collected in national and international graduate surveys - REFLEX, REFLEX 2010, REFLEX 2013, and Absolvent 2018. The data for contextual variables come from Eurostat and the Czech Statistical Office. The analyses focus on graduates four to five years after graduation. They are examined both as a whole and in groups based on the field of study using the method of weighted least squares. Overeducation usually has significant negative effects on earnings. Horizontal match effects are contradictory. The education-job (mis)match effects are relatively small in comparison with other factors. The role of contextual variables is mostly predictable, however, some exceptions uncover specifics of the labour market in the Czech Republic. There are important differences among groups of graduates in different fields of study.
Keywords: I23; J20; J21; J23; J24; J30; 330; education-job (mis)match; earnings; graduates; higher education; labour market